Memorials and shifting meanings of rural revolts in South Africa: the Mpondo rural revolts and insurgent scholarship - Kepe, Thembela (Review of African political economy, 2024)
This article uses the case of the commemoration of the Mpondo Revolts and the massacre by the state of defenceless villagers in Mpondoland in 1960 to argue that the political elite engage in distortions of history for political gain. The ruling party elite have over time omitted or added narratives about the revolts, thus gradually marginalising their significance. Part of the distortion of the history of the revolts is the gradual attempt to change the conversation during the annual commemoration event of the revolts and the Ngquza Hill massacre. While local people continue to be disenfranchised from their land, ironically now by the post-apartheid government, politicians at the memorial event focus not on the issues that were the causes of the revolts, especially the struggles around land, but on apparent local needs, such as electrification, access to clean water and bringing revenue to the villages through tourism. However, memorialisation of historical events is prone to these contested histories and narratives because of the political and financial support of the government in power, institutionalising both tangible and intangible aspects of the history that is being memorialised. It is only through defiant or insurgent scholarship that more accurate versions of the history of events such as the Mpondo Revolts can help to maintain their significance.